Dental practitioners’ knowledge, attitudes, and practices of ergonomics – a cross-sectional web-based survey - Galla, Anusha; Chowdhry, Anusuya; Bagga, Aayushi; Moradia, Lohan; Tadikonda, Abhinav; Pentapati, Kalyana; Mysore, Nanditha-Kumar (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Dentistry is a profession known to have many occupational hazards, including biomechanical, ergonomic, and work factors. We aimed to evaluate dental practitioners’ knowledge, attitudes, and practices of ergonomics and to evaluate the significant differences with age, sex, educational qualification and clinical experience.Methods: We conducted a cross-sectional multi-centric web-based survey among dental practitioners of south India. Dentists who were involved in clinical practice in India with a minimum of 1-year experience were invited to participate in this study. Information on demographics (age, sex, education) and years of practice of the dental practitioners was collected. Knowledge attitude and practice questionnaire was adapted from El Salamy et al.Results: The mean age of the participants was 30.57 (SD=6.95). More than half of the respondents were female (60.1%). Dental practitioners who were less than 28 years old (OR: 0.57), graduates (OR: -0.47), and clinical experience less than three years (OR: -0.53) had a higher probability of having poor or fair knowledge scores. Dental practitioners who were more than 28 years old had a significantly higher probability of positive attitudes (OR: 0.6) and good practices (OR: 0.54). Practitioners with a master’s degree had a higher probability of good practices (OR: 1.92). Practitioners with more than three years of clinical experience had a higher likelihood of good practices (OR: 1.72; 95% CI: 1.03 – 2.9).Conclusions: Overall, we could conclude that dental professionals had predominantly fair to good knowledge, positive attitudes and a high proportion of bad practices.